2020
DOI: 10.1093/mnras/staa1655
|View full text |Cite
|
Sign up to set email alerts
|

Binary-induced spiral arms inside the disc cavity of AB Aurigae

Abstract: ABSTRACT In this work we demonstrate that the inner spiral structure observed in AB Aurigae can be created by a binary star orbiting inside the dust cavity. We find that a companion with a mass-ratio of 0.25, semimajor axis of 40 au, eccentricity of 0.5, and inclination of 90° produces gaseous spirals closely matching the ones observed in 12CO (2-1) line emission. Based on dust dynamics in circumbinary discs (Poblete, Cuello & Cuadra 2019), we constrain the i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 75 publications
3
24
0
Order By: Relevance
“…We can safely exclude the 𝜃 = 60 • case, because both the reduced cavity size and the lack of azimuthal over-density make this case significantly different from the observations. Non-coplanarity between the binary and the circumbinary disc has been previously invoked to explain the morphology in a number of systems (Price et al 2018b;Calcino et al 2020;Poblete et al 2020;Ballabio et al 2021). This highlights that misaligned geometries are not particularly exotic and is in agreement with the results by Czekala et al (2019), who found that distribution of binary-disc inclination is relatively flat for long period binaries.…”
Section: Discussionsupporting
confidence: 85%
“…We can safely exclude the 𝜃 = 60 • case, because both the reduced cavity size and the lack of azimuthal over-density make this case significantly different from the observations. Non-coplanarity between the binary and the circumbinary disc has been previously invoked to explain the morphology in a number of systems (Price et al 2018b;Calcino et al 2020;Poblete et al 2020;Ballabio et al 2021). This highlights that misaligned geometries are not particularly exotic and is in agreement with the results by Czekala et al (2019), who found that distribution of binary-disc inclination is relatively flat for long period binaries.…”
Section: Discussionsupporting
confidence: 85%
“…These illumination features are thought to be caused by a misaligned inner disc that obstructs the stellar light (Marino et al 2015;Min et al 2017). The detailed modelling of individual sources, such as HD 142527 (Price et al 2018b) and AB Aur (Poblete et al 2020), shows how a circumprimary disc can form from the infalling material in the presence of an eccentric and inclined companion inside the disc cavity.…”
Section: Discussionmentioning
confidence: 99%
“…Pinte et al 2018Pinte et al , 2019 and stellar companions (e.g. Calcino et al 2019;Poblete et al 2020) in the disc. Determining the origin of the twist in MWC 758 will help refine our model, as whether it originates due to an inclined inner disc, or radial flows, can imply different consequences for our companion (e.g.…”
Section: Co Emissionmentioning
confidence: 99%
“…We acknowledge use of the OzStar supercomputing facility, funded by Swinburne University and the Australian Government. we used SPLASH and PLONK for visualisation of our simulations (Price 2007;Mentiplay 2019).…”
Section: Acknowledgementsmentioning
confidence: 99%